A captação de recursos à pesquisa e ao stricto sensu no Estado de São Paulo: um estudo de caso múltiplo - Nishimura, Mari Mitsuru (2017)
The study herein aims to identify competitive strategies, and financial resource attraction for investment on research and Master’s degrees and Doctorate programs, as well as analyse how relationship with stakeholders contributes to develop an efficient university management. To do so, both a bibliographical review and a multi-case study have been undertaken. Theoretical review involves: 1) concepts and forms, strategies and sustainability of financial resource attraction at both Brazilian and foreign institutions; 2) relationship marketing with its concepts and as a strategy at the IES (Higher Education Institutions), which also involves stakeholder’s management. An empirical and qualitative research, by means of a multi-case study method has been developed in three research units reffered to as A, B, and C with institutional support for research offices or similar. Results show that each unit has their own financial resource attraction practices, among which unit A has stood out once they have a well structured office, with qualified and competitive services offered to the researcher. It has been observed EAIP (Research Support Office) relevance is not restricted to operational aspects but in fact it lies mainly in its strategic importance. As for contributions this study may bring, it has carried out a comparative analysis of the results of financial resource attraction and the relationship of stakeholders from the perspective of a research support office.